The Effects of Tai Chi and Qigong Exercise on Psychological Status in Adolescents: A Systematic Review and Meta-Analysis - Liu, Xuan; Li, Ru; Cui, Jiabao; Liu, Fang; Smith, Lee; Chen, Xiaorong; Zhang, Debao (Frontiers in Psychology, 2021)
Background: The purpose of this study was to systematically review the effectiveness of Tai Chi and Qigong exercise on adolescents’ symptoms of depression and anxiety, and psychological status based on clinical evidences, and to calculate the pooled results using meta-analysis. Methods: A systematic search using seven English and three Chinese databases was initiated to identify randomized controlled trials (RCT) and non-randomized comparison studies (NRS) assessing the effect of Tai Chi and Qigong exercise on psychological status among adolescents. Standardized mean differences (SMD) and their 95% confidence intervals (CI) were used to determine the pooled effect of the intervention. Study quality was evaluated using a Checklist to Evaluate a Report of a Nonpharmacological Trial (CLEAR-NPT) designed for nonpharmacological trials. Results: Four RCTs and six NRS were identified, including 1244 adolescents. The results suggested a potential beneficial effect of Tai chi and Qigong exercise on reducing anxiety (SMD=0.386, 95CI% [0.233, 0.538]) and depression (SMD=1.937 [95CI%,1.392-2.546]) symptoms, and reducing cortisol level (SMD=0.621 [95CI%,0.18-1.062]) in adolescents. Conversely, non-significant effects were found for stress, mood, and self-esteem. Conclusions: The findings of this review suggest Qigong appears to be an effective therapeutic modality to improve psychological well-being in adolescents. Hope future studies will have rigorously designed, well-controlled randomized trials with large sample sizes in order to confirm these findings.